2013
DOI: 10.1016/j.proeps.2013.03.095
|View full text |Cite
|
Sign up to set email alerts
|

Understanding CO2 Gas Production Above a Partly Flooded, Former Coal Mining Area

Abstract: International audienceINERIS has worked for several years on the characterization of O2-defficient and CO2-enriched gas production and migration processes above a partly flooded, former coal mining area. To understand the origin of this gas production, a borehole 90 meters deep was drilled next to the area of gas emmanation. Several investigations were conducted to improve the understanding of the gas production mechanisms in relation to the presence of water. This paper deals with the results of experiments c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Example of a negative obtained with the SEM (Lagny et al, 2013) Marcasite (or white iron pyrite) was found on several samples both in a pristine and a partially oxidised state. It is a ferrous sulphide mineral which is more easily oxidised than pyrite.…”
Section: Figmentioning
confidence: 99%
“…Example of a negative obtained with the SEM (Lagny et al, 2013) Marcasite (or white iron pyrite) was found on several samples both in a pristine and a partially oxidised state. It is a ferrous sulphide mineral which is more easily oxidised than pyrite.…”
Section: Figmentioning
confidence: 99%
“…Lack of charging in the shaft is an unfavorable situation in terms of the emission of mine gases into the atmosphere as well as in terms of safety in the vicinity of the shaft. In the GZW area, gases can flow through them hydraulically [21].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of environmental protection and gas hazards at the surface, two gases are the most important: carbon dioxide (CO 2 ) and methane (CH 4 ) (Bateson et al, 2008;Cheng et al, 2011;Beaubien et al, 2013;Lagny et al, 2013;Feitz et al, 2014;Jones et al, 2014). They are both considered to be greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%